The prognostic value of plasma complement factor B (CFB) in thyroid carcinoma. Issue 2 (20th December 2021) - Wu, Pu; Shi, Jinyuan; Sun, Wei; Zhang, Hao
ABSTRACT: Stromal and immune cells are major components of tumor microenvironment (TME) and affect the growth and development of thyroid carcinoma (THCA). However, data on the exact mechanisms that define the relationship between the TME and THCA remain scant. We calculated stromal and immune cells scores and the proportion of tumor-infiltrating immune cells (TICs) by CIBERSORT and ESTIMATE based on the THCA gene expression data from the Cancer Genome Atlas (TCGA). In addition, we evaluated differentially expressed genes (DEGs) from high- and low-score groups and performed functional enrichment analysis. Furthermore, our data show a significant correlation between plasma complement factor B (CFB) and PTC development and prognosis. Gene Set Enrichment Analysis (GSEA) demonstrated that the CFB was mainly enriched in immune response pathways. The expression of CFB was positively correlated with T cells CD8, Macrophages M1, Plasma cells, T cells CD4 memory activated, T cells follicular helper and T cells regulatory (Tregs), whereas negatively correlated with Eosinophils, Macrophages M0, Macrophages M2, Mast cells resting, T cells CD4 memory resting in the TME. Finally, the expression level of CFB was verified by other cohorts from Gene Expression Omnibus (GEO) database and quantitative Real-Time PCR (qRT-PCR) analyses, which was consistent with the results of bioinformatic analysis. Taken together, our data demonstrated that the CFB could be a prognostic marker for THCA and its expression influences the infiltration of immune cells.